Potential role of P2X7 receptor in regulating kidney stem cells in the course of acute kidney injury (Bangladesh Journal of Pharmacology, 2016)
The role of the P2X7R in developing acute kidney injury is unknown. In this study, we  developed acute kidney injury mouse model system using 0.75% adenine and examined for renal damage using histology on day 2 and day 4. P2X7 antagonist (A438079) was used to study the recovery process after initial damage and it shows positive histological data. The P2X7R expression on the day 2 and day 4 of acute kidney injury was studied using immunohisto-chemistry and Western blotting. Result shows elevated expression as acute kidney injury progress. Later the P2X7R expression was compared with apoptotic signal and stem cell specific marker (CD133).  The results conclude that the apoptotic signals are mainly associated with advanced stage of acute kidney injury but not much in day 2. Similarly, CD133 expression was mask-ed in latter stages of injury following elevated expression in the initial stages.